Country variations in depressive symptoms profile in Asian countries: Findings of the Research on Asia Psychotropic Prescription (REAP) studies. (13th January 2015) - Chee, Kok‐Yoon; Tripathi, Adarsh; Avasthi, Ajit; Chong, Mian‐Yoon; Xiang, Yu‐Tao; Sim, Kang; Si, Tian‐Mei; Kanba, Shigenobu; He, Yan‐Ling; Lee, Min‐Soo; Fung‐Kum Chiu, Helen; Yang, Shu‐Yu; et al.
Abstract Introduction This study was to assess differences in the symptom profile of depressive illness across various countries/territories in Asia. The study was a part of the Research on Asia Psychotropic Prescription project. The participating countries/territories include China, Hong Kong, India, Indonesia, Japan, Korea, Malaysia, Singapore, Taiwan, and Thailand. Methods The pattern of depressive symptoms in 1, 400 subjects with depressive disorder from 42 psychiatric centers in 10 Asian countries/territories was assessed. We collected information on socio‐demographic and clinical characteristics with a standardized protocol and data collection procedure. Results The most common presentations of depressive symptoms were persistent sadness, loss of interest, and insomnia. Similar findings were found regardless of the region, country, or its income level. Patients with depressive disorder from high‐income countries presented significantly more with vegetative symptom cluster (P < 0.05), while those from the upper middle‐income countries had significantly more with both mood (P < 0.001) and cognitive symptom clusters (P < 0.01). In lower middle‐income countries, patients with depressive symptoms had significantly less mood symptom cluster (P < 0.001) but significantly more cognitive symptom cluster (P < 0.05). Discussion This study demonstrates that in Asia, despite variations in the initial symptom reported by the patients, across different countries/territories, core depressive symptoms remain the same. Variations have been found in presentation of depressive symptoms with regards to the level of income of countries. Physical or vegetative symptoms were reported more by centers in higher income countries, while depressive cognition and suicidal thoughts/acts were more frequently reported from lower income countries.